Simulation Study on the Dynamic Ventilation Control of Single Head Roadway in High-Altitude Mine Based on Thermal Comfort - Xingxin Nie; Shanshan Feng; Zhang Shudu; Gan Quan (Advances in Civil Engineering)
Dynamic ventilation control based on the concept of thermal comfort is proposed and applied to single head roadway in high-altitude gold mine in Qinghai. Hourly thermal comfort values are determined for typical working conditions, and a thermal comfort curve is generated. The values are adjusted based on the external environment and the changes in the miners’ thermal comfort. The Fluent software is used to simulate the temperature field and wind speed field of the tunnel roadway at three heights, and the results are used to fit the thermal comfort curve in the roadway. The results show that the thermal comfort is lowest at a roadway height of 1 m and a longitudinal length of 16 m because the wind speed is the highest and the temperature is lowest at these locations. When the dynamic ventilation control is used, the optimal thermal comfort levels can be determined for the locations in the single head roadway.